RESTORATIVE JUSTICE APPROACH IN CRIMINAL CASE SETTLEMENT AT CIREBON POLICE: EFFORTS TO REALIZE LEGAL CERTAINTY AND JUSTICE - Salma Nur Khalisha; Ismayana Ismayana; Yanti Romlahayati (Fakultas Hukum Universitas Swadaya Gunung Jati, 2026)
This study is motivated by the development of the restorative justice approach in resolving criminal cases, particularly embezzlement cases, at the investigative stage. The restorative justice approach is viewed as an alternative method of case resolution that focuses not only on punishing the perpetrator but also on compensating the victim and directly resolving the conflict between the parties. The research question in this study is how restorative justice is applied and legally protected during the investigative stage in embezzlement cases at the Cirebon City Police Department. The research method used is normative legal research, employing a statutory and case study approach. Data were obtained through a literature review, interviews, and documentation, and were analyzed qualitatively. The results of the study indicate that restorative justice is implemented through a mediation process between the perpetrator and the victim, taking into account relevant conditions. In the case studied, the perpetrator returned the victim's car as a form of restitution, thereby resolving the case without proceeding to formal criminal court proceedings. The application of restorative justice is considered quite effective because it resolves conflicts directly, provides redress to victims, and serves as an increasingly simple and efficient alternative method for handling cases. It can be concluded that the application of restorative justice in embezzlement cases during the investigation stage can serve as an effective case resolution approach grounded in the principle of restitution; however, its implementation must still adhere to applicable legal provisions to ensure that the objectives of justice and legal certainty are maintained in a balanced manner.